PENINGKATAN PEMAHAMAN MATERI PESAWAT SEDERHANA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIVEMENT DIVISION) DI MINU NGINGAS WARU SIDOARJO - Rohmah, Nurul Hidayatur (Journal Of Islamic Elementary School (JIES), 2019)
The learning process of Natural Sciences that occurred at MINU Waru did not develop students 'thinking skills so that students' understanding was less satisfying. This study aims to test the effectiveness of the implementation of cooperative learning models of Student Teams Achievement Division (STAD) in improving students' understanding. The research model used is the Classroom Action Research (CAR) model adapted from Lewin's curse. The results of the study showed: (1) Application of cooperative learning models to improve simple aircraft material for science subjects in class V students of MINU Ngingas Waru Sidoarjo showed that in the first cycle based on the observation of teacher activities and student activities still below the completeness criteria of 80. In the first cycle the score the teacher gets 74.25 (enough) and the student activity score gets 71.42 (enough) in the second cycle the teacher's activity gets 93.75 (very good) and student activities 89.65 (good), from these results it can be said that the researcher has achieve a predetermined performance indicator, which is 80; (2) The level of students' understanding of simple aircraft material in science subjects in class V MINU Ngingas Waru Sidoarjo has increased from pre-cycle, cycle I and cycle II, seen in the results of the percentage of completeness of students in pre-cycle activities that is 37.14% (less) , cycle I is 60% (sufficient), cycle II is 88% (good). The next increase can be seen from the results of the average score of students in pre-cycle activities, namely getting 57 (less), cycle I getting 70.5 (enough), and cycle II getting 84.7 (good). Students in class V MINU Ngingas numbered 35 students, the results obtained that students who completed the pre-cycle activities amounted to 13 students completed, the first cycle amounted to 21 students completed and the second cycle amounted to 31 students completed.